2015
DOI: 10.1371/journal.pone.0112021
|View full text |Cite|
|
Sign up to set email alerts
|

Implications of the Circumpolar Genetic Structure of Polar Bears for Their Conservation in a Rapidly Warming Arctic

Abstract: We provide an expansive analysis of polar bear (Ursus maritimus) circumpolar genetic variation during the last two decades of decline in their sea-ice habitat. We sought to evaluate whether their genetic diversity and structure have changed over this period of habitat decline, how their current genetic patterns compare with past patterns, and how genetic demography changed with ancient fluctuations in climate. Characterizing their circumpolar genetic structure using microsatellite data, we defined four cluster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
110
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 51 publications
(119 citation statements)
references
References 99 publications
(158 reference statements)
9
110
0
Order By: Relevance
“…Previous analysis of polar bear population structure using microsatellites showed no significant genetic differences between BB and neighboring KB (Paetkau et al., 1999), though studies have found that bears from BB‐KB differed genetically from the LS and DS subpopulations (Paetkau et al., 1999; Peacock et al., 2015; Malenfant et al., 2016). In contrast, we found low but significant F ST estimates between winter–spring samples from BB and KB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous analysis of polar bear population structure using microsatellites showed no significant genetic differences between BB and neighboring KB (Paetkau et al., 1999), though studies have found that bears from BB‐KB differed genetically from the LS and DS subpopulations (Paetkau et al., 1999; Peacock et al., 2015; Malenfant et al., 2016). In contrast, we found low but significant F ST estimates between winter–spring samples from BB and KB.…”
Section: Discussionmentioning
confidence: 99%
“…While these samples were collected and analyzed primarily for a genetic mark–recapture (MR) assessment (SWG, 2016), the eight polymorphic microsatellites selected were used in population genetic analyses with the objective of assessing differentiation between BB and neighboring subpopulations. As the samples were recent and temporally congruent, these analyses provided an update to past population genetic studies (Paetkau et al., 1999; Peacock et al., 2015; Malenfant, Davis, Cullingham, & Coltman, 2016) that used samples from the 1990s. We used standardized population genetic analytical tools and methods to investigate genetic connectivity between subpopulations (ADEGENET package, Jombart, 2008; ARLEQUIN Version 3.5.1, Excoffier & Lischer, 2010; BA3‐3.0.3, Wilson & Rannala, 2003; DAPC, Jombart, Devillard, & Balloux, 2010; FSTAT, Goudet, 1995; GENECLASS2, Piry et al., 2004; GENELAND, Guillot, Mortier, & Estoup, 2005; Guillot, 2008; STRUCTURE, Pritchard, Stephens, & Donnelly, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…We used blood and skin samples from FB, SH, and WH polar bears as well as from the adjacent Davis Strait subpopulation (DS) because of its intermediate genetic relationship to the Hudson Bay region and the Canadian Archipelago (Malenfant et al., 2016; Obbard et al., 2010; Paetkau et al., 1999; Peacock et al., 2015). Samples were collected between 2004 and 2010 for SH ( n  = 112) and WH ( n  = 120) from capture–recapture studies conducted by the Ontario Ministry of Natural Resources and Forestry and Environment and Climate Change Canada, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Global‐scale studies generally supported the currently designated 19 subpopulations used for management purposes (Obbard, Thiemann, Peacock, & DeBruyn, 2010; Paetkau et al., 1999; Peacock et al., 2015), whereas regional studies show differentiation between adjacent subpopulations (e.g., Campagna et al., 2013). Although the first global‐scale studies defined the Hudson Bay region as a single unique genetic cluster (Paetkau et al., 1999), this study did not include samples from SH, and more recent fine‐scale studies that included samples from SH (Crompton et al., 2008, 2014; Malenfant et al., 2016; Peacock et al., 2015) identified substructure within Hudson Bay, specifically, a unique population in James Bay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation